2010
DOI: 10.1177/2040622310382817
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers in Alzheimer’s disease therapeutics

Abstract: Alzheimer disease (AD) is a progressive neurodegenerative disease which begins with insidious deterioration of higher cognition and progresses to severe dementia. Clinical symptoms typically involve impairment of memory and at least one other cognitive domain. Because of the exponential increase in the incidence of AD with age, the aging population across the world has seen a congruous increase AD, emphasizing the importance of disease altering therapy. Current therapeutics on the market, including cholinester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 163 publications
(201 reference statements)
0
17
0
Order By: Relevance
“…Considerable research has focused on the neurotoxicity of beta amyloid peptides (Aβ) since they were identified in plaques from AD patients decades ago (Goate and Hardy, 2012; Holtzman et al, 2011; Selkoe, 1993), yet therapeutic studies targeting Aβ have yielded disappointing or counterproductive results (Aisen et al, 2011; Galimberti and Scarpini, 2011; Karran et al, 2011; Selkoe, 2011b; Stone et al, 2011). Among other things, impediments to progress in this arena might reflect uncertainty regarding the relevant Aβ species to target (Benilova et al, 2012), the use of inconsistent model systems or supraphysiologic Aβ peptide concentrations (Castellani and Smith, 2011; Waters, 2010), incomplete understanding of physiologic versus pathologic roles of Aβ and amyloid precursor protein (APP) (Chasseigneaux and Allinquant, 2012; Guo et al, 2012; Zhang et al, 2012), and incomplete consideration of alternative pathogenic mechanisms, particularly those affecting synapses (Chakroborty and Stutzmann, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has focused on the neurotoxicity of beta amyloid peptides (Aβ) since they were identified in plaques from AD patients decades ago (Goate and Hardy, 2012; Holtzman et al, 2011; Selkoe, 1993), yet therapeutic studies targeting Aβ have yielded disappointing or counterproductive results (Aisen et al, 2011; Galimberti and Scarpini, 2011; Karran et al, 2011; Selkoe, 2011b; Stone et al, 2011). Among other things, impediments to progress in this arena might reflect uncertainty regarding the relevant Aβ species to target (Benilova et al, 2012), the use of inconsistent model systems or supraphysiologic Aβ peptide concentrations (Castellani and Smith, 2011; Waters, 2010), incomplete understanding of physiologic versus pathologic roles of Aβ and amyloid precursor protein (APP) (Chasseigneaux and Allinquant, 2012; Guo et al, 2012; Zhang et al, 2012), and incomplete consideration of alternative pathogenic mechanisms, particularly those affecting synapses (Chakroborty and Stutzmann, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Since the loss of cholinergic activity is a major trait observed in AD, the current first‐line treatment for AD is acetylcholinesterase (AChE) inhibitors (Álvarez and Fuentes,2011; Farlow and Cummings;2007, Stone et al,2011) such as donepezil, rivastigmine, tacrine, and galantamine (Craig et al,2011; Seow and Gauthier,2007). The most widely prescribed drug for AD treatment is donepezil (Craig et al,2011; Tsuno,2009).…”
Section: Introductionmentioning
confidence: 99%
“…Today, multiple therapies for AD are being studied [62,70,71]. The progress in the knowledge of the molecular characteristics of the disease and the availability of several animal models for study, it has open the boundaries to test and develop new therapies [61,62,72], for example, strategies for modifying AD progression include reducing neuroinflammation, metabolic approaches such as lipid-lowering agents, estrogen, antioxidants, anti-Aβ immunotherapy and recent neurotrophin-based approaches [62,69,72,73]. In this scenario, and given the importance and the temporality of mitochondrial damage in AD, we believe that mitochondrial-targeted therapeutic strategies are one of the most promising areas of interest.…”
Section: Improving Mitochondrial Health As a Valid Therapy For Admentioning
confidence: 99%